Trends in Interactive Visualization State-of-the-Art Survey - Zudilova-Seinstra, Elena; Adriaansen, Tony; van Liere, Robert (Advanced Information and Knowledge Processing, 2009)
This unique, multi-disciplinary volume provides an insight into an active and vital area of research - Interactive Visualization. Interactive Visualization enables the development of new scientific techniques to view data, and to use interaction capabilities to interrogate and navigate through datasets and better communicate the results. A wide range of topics are covered in this important new book, representing the state of the art in this research area and providing a special emphasis on: • Advanced data representation; • Integration of visualization and modelling techniques; • Novel user interfaces for data exploration and analysis; • Virtual environments and collaborative visualization; • Design and evaluation of interactive visualization tools and systems. Students and researchers in scientific and information visualization, virtual reality, human-computer interaction, interface and interaction design, computer graphics and multimedia will find the book an excellent survey of this exciting field.